IMPLEMENTATION OF MURABAHAH PRODUCT MARKETING STRATEGY OF SHARIA PUBLIC FINANCING BANK (BPR SHARIA) - Wawan Susanto; Novrida Qudsi Lutfillah; Soenarmi .; Yuyun Widiastuti (Manajemen dan Bisnis, 2017)
This study aims to understand the implementation of marketing strategies for murabahah products in BPR Sharia in Lamongan. The research method used is a case study by interviewing the head and account officer of BPR Sharia Lamongan Branch as interviewees. The results showed that murabahah products in the implementation of marketing strategies applying a service marketing mix that has been adapted to the environment where BPR Sharia Lamongan Branch was located, including: (1) murabahah products that are sharia-based, (2) promotion using socialization strategies as well as sharia banking education programs, (3) an easy process, and (4) employees (human resources) who have honesty, trusteeship, and politeness, and can establish a family-like relationship with customers. The implementation of marketing strategies is interpreted as keeping trust entrusted to the welfare of the people.